Floristic inventory of forest genetic resources reserve in Korea - Yun, Ho-Geun; Jung, Ji-Young; Shin, Hyun-Tak; An, Jong-Bin (Journal of Asia-Pacific biodiversity, 2021)
This study was based on a 12-year survey data on the distribution of vascular plants between 2007 and 2019 in forest genetic resource reserves designated and managed by the Korea Forest Service. A total of 2,039 taxa were identified, which comprised 1,819 species, 33 subspecies, 161 varieties, and 26 forms from 703 genera and 154 families. There were 149 taxa of Korean endemic plants in the study area. There were 198 taxa of rare plants, with 28 critically endangered (CR) taxa 46 endangered (EN) taxa, 68 vulnerable (VU) taxa, 56 taxa of least concern (LC) taxa. There were a total of 739 taxa of floristic target species, Category V (52 taxa), Category IV (178 taxa), Category III (218 taxa), Category II (131 taxa), Category I (160 taxa). There were 1,312 taxa of useful plants: 580 taxa of plants used for pasture (P), 512 taxa of edible plants (E), 455 taxa of medicinal plants (M), 257 taxa of ornamental plants (O), 59 taxa of plants used for timber (T), 48 taxa of plants used for staining (S), 22 taxa of plants used for fiber (F) and 9 taxa of industrial plants (R).